2006
DOI: 10.21236/ada449172
|View full text |Cite
|
Sign up to set email alerts
|

A Regional Guidebook for Applying the Hydrogeomorphic Approach to Assessing Wetland Functions of Prairie Potholes

Abstract: ABSTRACT:The Hydrogeomorphic (HGM) Approach is a method for developing functional indices and the protocols used to apply these indices to the assessment of wetland functions at a site-specific scale. The HGM Approach was initially designed to be used in the context of the Clean Water Act, Section 404 Regulatory Program, permit review to analyze project alternatives, minimize impacts, assess unavoidable impacts, determine mitigation requirements, and monitor the success of compensatory mitigation. However, a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 75 publications
(112 reference statements)
1
11
0
Order By: Relevance
“…The complexity of the wetland perimeter described above can be quantified in terms of the SI, calculated as the ratio of the actual wetland perimeter to the perimeter of a circle of equivalent area, as shown in (Merendino and Ankney 1994, Gilbert et al 2006). A comparison of the SI between current and historical wetlands shows a value of 2.43 ± 1.28 for historical wetlands and 1.56 ± 0.60 for current wetlands; all means are presented ±standard deviation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The complexity of the wetland perimeter described above can be quantified in terms of the SI, calculated as the ratio of the actual wetland perimeter to the perimeter of a circle of equivalent area, as shown in (Merendino and Ankney 1994, Gilbert et al 2006). A comparison of the SI between current and historical wetlands shows a value of 2.43 ± 1.28 for historical wetlands and 1.56 ± 0.60 for current wetlands; all means are presented ±standard deviation.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of multiple wetland ponds in Saskatchewan, Canada between 1963 and 1969, observed a strong linear correlation between infiltration losses from ponds and the P : A ratio. These findings suggest that rates of water loss, and thus the potential for recharge, from prairie potholes will vary directly with the P : A ratio and hence inversely with the size of individual wetlands (Gilbert et al 2006). Accordingly, the reduction in the P : A ratio that has occurred between historical and current wetlands translates to disproportionate losses in their recharge function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several assessment protocols are available. Protocols in wide use in Montana range from rapid assessments of Proper Functioning Condition (Pritchard, 2003) to the Montana Department of Transportation's Montana Wetland Assessment Method for highway projects (Berglund and McEldowney 2008) to Army Corps of Engineers' Hydrogeomorphic (HGM) Method for Prairie Potholes (Gilbert et al 2006). Over the past several years, the Montana Natural Heritage Program (MTNHP) has been refining a protocol for assessing the ecological integrity of wetlands, using the three-tiered approach recommended by the U.S. Environmental Protection Agency: 1) a landscape-level assessment using GIS; 2) a rapid, semi-quantitative multimetric field assessment of wetland condition; and 3) a quantitative, vegetation-based method used to calculate indices of biological integrity.…”
Section: Restoration Areasmentioning
confidence: 99%
“…A wetland's position in the landscape (e.g., riparian, depressional, and lacustrine) is referred to as its hydrogeomorphic setting, which imparts controls on the relative sources of water (precipitation, groundwater, and surface water) to a wetland and their inherent hydrodynamic energies (Brinson, ). This approach is frequently adopted for wetland classification and assessment of hydrological, biogeochemical, and ecological functions, largely in a regulatory context (Smith, Ammann, Bartoldus, & Brinson, ; Cole & Brooks, ,b; Gilbert, Whited, Clairain, & Smith, ; Hill, Neary, & Morgan, ). Because the hydrogeomorphic setting is a strong control on the hydrology and soil physics and chemistry of a wetland, it also influences vegetation composition (Mitsch & Gosselink, ; Rheinhardt, ).…”
Section: Introductionmentioning
confidence: 99%